MODE-SELECTIVE CHEMISTRY IN THE REACTIONS OF OH WITH HBR AND HCL - Clary, D; Nyman, G; Hernandez, R (1994)
Quantum scattering calculations are reported for the reactions OH+HC1→H2O+Cl and OH+HBr→H2O+Br. The rotating bond approximation is used. This involves the explicit treatment of the bending vibration and local OH stretching vibration in H2O together with the vibration of HX (X=Cl,Br) and rotation of OH. Simple potential energy surfaces for the reactions are used which contain an accurate potential for H 2O. The transition state of the potential for the OH+HCl reaction agrees quite well with ab initio data. The most likely product vibrational state of H2O is the ground state for the OH(j =0)+HC1 reaction, and the combination band that has one quantum of energy in the H2O bending mode and one quantum in the local OH stretching mode of H2O for the OH(j=0)+HBr reaction. The reaction cross sections are found to depend on (2j + 1)-1, where j is the initial rotational quantum number of OH. This results in a T-1/2 dependence in the rate constant for the OH+HBr reaction at low temperatures, in agreement with experiment. © 1994 American Institute of Physics.